Nobelova nagrada 2021 za fiziko - Rakovec, Jože (Obzornik za matematiko in fiziko, 2022)
The Nobel Prize in Physics in 2021 was awarded "for groundbreaking contributions to our understanding of complex systems" - one half jointly to two meteorologists { Syukuro Manabe and Klaus Hasselmann "for the physical modelling of Earth's climate, quantifying variability and reliably predicting global warming" and the other half theoretical physicist Giorgio Parisi "for the discovery of the interplay of disorder and uctuations in physical systems from atomic to planetary scales" - and on this planetary scale, the areas of their research "met". In this article we describe what the winners discovered and how they came to these discoveries.
Keywords: klimatski modeli; meteorologija; naključnost; neurejenost